The molecular characteristics of colonic neoplasms in serrated polyposis: a systematic review and meta‐analysis. (22nd April 2016) - He, Emily Y.; Wyld, Lucy; Sloane, Mathew A.; Canfell, Karen; Ward, Robyn L.
Abstract: Serrated polyposis is a rare disorder characterised by the presence of multiple serrated polyps in the large intestine, and an increased personal and familial risk of colorectal cancer. Knowledge of the molecular characteristics of colonic lesions which develop in this syndrome is fragmented, making it difficult to understand the underlying genetic basis of this condition. We conducted a systematic review and meta‐analysis of all studies which evaluated the molecular characteristics of colorectal neoplasms found in individuals with serrated polyposis. We identified 4561 potentially relevant studies, but due to a lack of consensus in the reporting of findings, only fourteen studies were able to be included in the meta‐analysis. BRAF mutation was found in 73% (95% CI 65–80%) of serrated polyps, 0% (95% CI 0–3%) of conventional adenomas and 49% (95%CI 33–64%) of colorectal cancers. In contrast, KRAS mutation was present in 8% (95% CI 5–11%) of serrated polyps, 3% (95% CI 0–13%) of conventional adenomas and 6% (95% CI 0–13%) of colorectal cancers. Absence of MLH1 immunostaining was found in 3% (95% CI 0–10%) of serrated polyps and 53% (95% CI 36–71%) of colorectal cancers. Overall, microsatellite instability was found in 40% (95% CI 18–64%) of colorectal cancers arising in the setting of serrated polyposis. Our results indicate that diverse molecular pathways are likely to contribute to the increased predisposition for colorectal cancer in individuals with serrated polyposis. We also propose a set of minimum standards for the reporting of future research in serrated polyposis as this is a rare syndrome and collation of research findings from different centres will be essential to identify the molecular mechanisms involved in the pathogenesis of this condition.